(untitled) (Journal of Health, Population and Nutrition, 2010)
Pneumatosis intestinalis, in association with portal venous gas, is a rare finding in children and young adults. In radiological studies, it is characterized by gas-filled cysts within the bowel-wall. It is often a sign of the serious significant underlying illness and is associated with a poor prognosis. A case of pneumatosis intestinalis and portal venous gas associated with abdominal tuberculosis in a child is presented here. Despite responding well to anti-tubercular treatment, he died suddenly at home, two months after discharge. It is recommended that cases with pneumatosis intestinalis should be carefully observed, although symptoms appear to be improving. Key words: Case studies; Child; Pneumatosis intestinalis; Tuberculosis, Abdominal; Turkey DOI: 10.3329/jhpn.v28i6.6612 J HEALTH POPUL NUTR 2010 Dec;28(6):628-632